2022
DOI: 10.1002/jcla.24755
|View full text |Cite
|
Sign up to set email alerts
|

Metformin promotes smear conversion in tuberculosis‐diabetes comorbidity and construction of prediction models

Abstract: Background The comorbidity of tuberculosis (TB) and diabetes mellitus (DM) is a global health concern. Metformin is commonly used in DM but the potential effectiveness in comorbid patients is uncertain. This retrospective study aims to investigate the effect of metformin on TB‐DM comorbidity and construct prediction models. Methods Patients diagnosed with TB‐DM in West China Hospital were retrospectively enrolled from Nov 2013 to Sep 2019. Electronic health records of patients were extracted. Two‐month smear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These issues are paralleled in global studies, including Wang et al, who explore the potential role of metformin in improving TB treatment outcomes in TB-DM comorbidity, Wang et al, and Karoli et al, who examine the significance of vitamin D deficiency in managing TB-DM comorbidity. 16,17 Our findings of poorer outcomes and increased ADRs in TB-DM patients reflect the dual burden of these diseases, as underscored by Aweis et al and Babu et al 18,19 The study underscores the urgent need for integrated TB and DM management approaches, advocating for tailored treatment regimens, comprehensive patient education, and the utilization of advanced technologies like artificial intelligence. The study also highlights the importance of strengthening follow-up strategies and enhancing healthcare provider training to improve patient care and the outcomes for those affected by the TB-DM comorbidity.…”
Section: Discussionmentioning
confidence: 65%
“…These issues are paralleled in global studies, including Wang et al, who explore the potential role of metformin in improving TB treatment outcomes in TB-DM comorbidity, Wang et al, and Karoli et al, who examine the significance of vitamin D deficiency in managing TB-DM comorbidity. 16,17 Our findings of poorer outcomes and increased ADRs in TB-DM patients reflect the dual burden of these diseases, as underscored by Aweis et al and Babu et al 18,19 The study underscores the urgent need for integrated TB and DM management approaches, advocating for tailored treatment regimens, comprehensive patient education, and the utilization of advanced technologies like artificial intelligence. The study also highlights the importance of strengthening follow-up strategies and enhancing healthcare provider training to improve patient care and the outcomes for those affected by the TB-DM comorbidity.…”
Section: Discussionmentioning
confidence: 65%
“…Metformin could increase host cells production of mitochondrial ROS and the acidification of mycobacterium phagosome, promote the proliferation of T cells secreting IFN-γ, reduce the bacterial load, TB-induced tissue pathology and inflammatory response in both lung and spleen of mice, and enhance the host-specific immune function ( Singhal et al, 2014 ). Secondly, metformin treatment reduced soluble CD14, CD163, and inflammatory C-reactive protein levels in TB patients with diabetes, significantly decreased MMP-1, −2, −3, −7, −9, and − 12 levels, and promoted smear conversion, indicating that metformin has significant anti-inflammatory and lung injury improvement effects, and greatly reduced mortality ( Degner et al, 2018 ; Kumar et al, 2018 ; Kumar N. P. et al, 2019 ; Li et al, 2021 ; Wang Y. et al, 2022 ). In addition, metformin also could induce autophagy, regulate oxidative stress, and enhance the efficacy of anti-TB drugs ( Fatima et al, 2021 ).…”
Section: Repurposed Drugsmentioning
confidence: 99%
“…However, SASP could enhance the Mtb clearance activity of macrophages by activating NADPH oxidase to promote the oxidation of mycothiol in Mtb macrophages, rather than the metabolite-producing 5-aminosalicylic acid ( Cai et al, 2016 ). Previous studies have shown that SASP could significantly reduce the Mtb bactericidal load and histopathological inflammation of lungs in mice, and prevent severe inflammation induced by Mtb infection of human macrophages ( Cai et al, 2016 ; Wang Y. et al, 2022 ).…”
Section: Repurposed Drugsmentioning
confidence: 99%